Building and breaking a large igneous province: An example from the High Arctic. Issue 12 (17th June 2017) - Døssing, Arne; Gaina, Carmen; Brozena, John M.
Abstract: The genesis of the Amerasia Basin in the Arctic Ocean has been difficult to discern due to overprint of the Cretaceous High‐Arctic Large Igneous Province (HALIP). Based on detailed analysis of bathymetry data, new Arctic magnetic and gravity compilations, and recently published radiometric and seismic data, we present a revised plate kinematic model of the northernmost Amerasia Basin. We show that the smaller Makarov Basin is formed by rifting and seafloor spreading during the latest Cretaceous (to middle Paleocene). The opening progressively migrated into the Alpha Ridge structure, which was the focus of Early‐to‐Middle Cretaceous HALIP formation, causing breakup of the proto‐Alpha Ridge into the present‐day Alpha Ridge and Alpha Ridge West Plateau. We propose that breakup of the Makarov Basin was triggered by extension between the North America and Eurasian plates and possibly North Pacific plate rollback. Key Points: An early Aptian giant High‐Arctic LIP dyke swarm, >2000 km long, formed as part of early rifting of the Amerasia Basin Middle‐to‐Late Cretaceous HALIP flood basalts subsequently covered the northern Amerasia Basin, centered over the proto‐Alpha Ridge Latest Cretaceous to middle Paleocene rifting and seafloor spreading within the Makarov Basin broke apart the proto‐Alpha Ridge